Analisis Pengaruh Sistem Pengapian CDI Standar Dan Modifikasi Pada Motor Vario 110 CC - Irwan Suriaman; Robi A. Nurikhsan; Nefli Yusuf; T.B.U. Adi Subekhi; Choirul Anwar (Politeknik Negeri Jakarta, 2023)
Currently the use of motorcycles is increasing from year to year in Indonesia. The need for bicycles is increasingly important because its means of transportation, to make easier for users to carry out their daily activities. The existence of motorbikes in Indonesia is very important because they have several factors, namely having great power and fuel economy. Besides that, modifying motorbikes is one of the hobbies of Indonesian people with one of the reasons being the condition of the track in Indonesia. Modifying motorbikes is done by adding parts or changing the original components to get maximum results. Therefore, based on these problems, this research was conducted to test the performance of the vario motor for standard and modified CDI ignition systems. This test uses 2 types of fuel, namely pertalite and Pertamax. The measurement results from this study are using a dynamometer to measure various variations of engine speed to obtain motor power and torque. Based on research data, it was found that CDI modifications 1 and 2 with pertalite and Pertamax fuel had an influence on engine performance. Then for better results, namely the modification 2 CDI test with Pertamax fuel with the maximum power produced, namely 7.7 HP and 8.6 Nm of torque.